Attitude: Mediator of Subjective Norm, Religiosity and Intention to Adopt Islamic Banking - Bananuka, Juma; Kasera, Musa; Muganga, Grace Najjemba; Musimenta, Doreen; Ssekiziyivu, Bob; Kimuli, Saadat Nakyejwe Lubowa (Journal of Islamic Marketing., 2019)
The purpose of this paper is to report on the results of a study carried out to examine the mediating effect of attitude in the relationship between subjective norm, religiosity and intention to adopt Islamic banking in a developing secular state like Uganda. This study’ research design was cross sectional. Closed ended questionnaires were distributed to 258 managers of micro businesses in Uganda. Data were analyzed with the help of SPSS v22 and MedGraph program (Excel version).Attitude is a significant mediator in the relationship between subjective norm and intention to adopt Islamic banking. Also, attitude significantly mediates the relationship between religiosity and intention to adopt Islamic banking. The study used only a single research methodological approach; therefore, future research could be undertaken using a mixed-methods approach. Emphasis should be put on improving the mindsets of Ugandans toward Islamic banking. While there has been a number of studies on Islamic banking, this study provides an initial empirical evidence on the mediation effect of attitude in the relationship between subjective norm, religiosity and intention to adopt Islamic banking in a single study in an African developing secular state like Uganda.
Keywords: Uganda, Attitude, Subjective norm, Intention to adopt Islamic banking, Micro business